2021
DOI: 10.1007/s10984-021-09371-0
|View full text |Cite
|
Sign up to set email alerts
|

“We are much closer here”: exploring the use of WhatsApp as a learning environment in a secondary school mathematics class

Abstract: In this study, we examined a mathematics teacher’s communicative acts on an instant messaging tool, WhatsApp, and its role in creating a sustained learning environment between secondary-school students and a teacher in Turkey. The interactions of a mathematics teacher and his students ( n = 38) over two years were explored. The WhatsApp group increased interaction in out-of-school hours. Analysis of the teacher’s communicative acts was the leading force that encouraged the group to conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 54 publications
2
10
0
Order By: Relevance
“…This finding validates the results of some earlier studies (Yemi et al , 2018; Durgungoz and Durgungoz, 2021). These studies confirmed the increased interest shown by the students in Jigsaw collaborative learning sessions and WhatsApp-based collaborative learning.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding validates the results of some earlier studies (Yemi et al , 2018; Durgungoz and Durgungoz, 2021). These studies confirmed the increased interest shown by the students in Jigsaw collaborative learning sessions and WhatsApp-based collaborative learning.…”
Section: Discussionsupporting
confidence: 93%
“…The findings of the observation are in line with the existing research studies that implement collaborative learning with WhatsApp and simple online meeting software. Secondary school students' engagement and learning comfort with mathematics learning is found to be improved by increasing out-of-class teacher-student interaction by creating a digital learning environment (Durgungoz and Durgungoz, 2021).…”
Section: Collaborative Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…They stated that they enjoy being passive users of social media, and did not understand why teachers kept separate/private social media accounts. Durgungoz and Durgungoz (2021) examined the usage of a specific social media application, namely WhatsApp, by a teacher and his students. As school and residences were located far away, students mentioned that the online group offered a "meeting point" where they motivated and helped each other with schoolwork.…”
Section: Social Media and Chat Functionsmentioning
confidence: 99%
“…These outcomes encompass a wide range of factors, including instructional effectiveness and the development of prosocial behaviour. In addition, Durgungoz and Durgungoz (2022) believe these relationships are essential for establishing a social presence in class. According to research, the frequency, quality, and form of classroom interactions influence social presence more precisely.…”
Section: Introductionmentioning
confidence: 99%